Development of symptomatic brain metastases after chemoradiotherapy for stage III non-small cell lung cancer: Does the type of chemotherapy regimen matter?. (November 2016) - Hendriks, Lizza E.L.; Brouns, -->Anita J.W.M.; Amini, Mohammad; Uyterlinde, Wilma; Wijsman, Robin; Bussink, Jan; Biesma, Bonne; Oei, S. Bing; Stigt, Jos -->A.; Bootsma, Gerben P.; Belderbos, José S.A.; De Ruysscher, Dirk K.M.; et al.
Highlights: ⿢ 18% of chemoradiation treated stage III NSCLC develop symptomatic brain metastases. ⿢ Symptomatic brain metastases development is not dependent on specific chemotherapy. ⿢ Other modifiable factors should be studied that reduce brain metastases development. Abstract: Objectives: Symptomatic brain metastases (BM) occur frequently after chemoradiotherapy (CRT) for stage III NSCLC. Aim of the current study was to determine whether the specific chemotherapy used in a CRT regimen influences BM development. Materials and methods: Retrospective multicenter study including all consecutive stage III NSCLC who completed CRT. Primary endpoints: symptomatic BM development, whether this was the only site of first relapse. Differences between regimens were assessed with a logistic regression model including known BM risk factors and the specific chemotherapy: concurrent versus sequential (cCRT/sCRT), within cCRT: daily low dose cisplatin (LDC)-cyclic dose polychemotherapy; LDC-(non-)taxane cyclic dose; LDC⿿polychemotherapy subgroups of ⿥50 patients. Results: Between January 2006 and June 2014, 838 patients were eligible (737 cCRT, 101 sCRT). 18.2% developed symptomatic BM, 8.0% had BM as only site of first relapse. BM patients were significantly younger, female, had more advanced N-stage and had adenocarcinoma histology. In both cCRT and sCRT BM were found in 18% ( p  = 0.904). In cyclic dose cCRT ( N  = 346) and LDC ( N  = 391) BM were found in 18.8% and 17.9%, respectively ( p  = 0.757). In 7.2% and 8.7%, respectively, BM were the only site of first relapse ( p  = 0.463). The chemotherapy used (cCRT versus sCRT) had no influence on BM development, not for all brain relapses nor as only site of first relapse (OR 0.88 ( p  = 0.669), OR 0.93 ( p  = 0.855), respectively). LDC versus cyclic dose cCRT was not significantly different: neither for all brain relapses nor as only site of first relapse (OR 0.96 ( p  = 0.819), OR 1.21 ( p  = 0.498), respectively). Comparable results were found for LDC versus cyclic dose non-taxane ( N  = 277) and cyclic dose taxane regimens ( N  = 69) and for cCRT regimens with ⿥50 patients (LDC versus cisplatin/etoposide ( N  = 188), cisplatin/vinorelbin ( N  = 65), weekly cisplatin/docetaxel ( N  = 60)). Conclusion: approximately 18% developed symptomatic BM after stage III diagnosis, not dependent on type of chemotherapy regimen used within a CRT treatment.